Empowering Islamic Religious Teachers: Professional Development and Challenges - Adri Lundeto (GoAcademica Research & Publishing, 2023)
Professional development for Islamic religious teachers plays a pivotal role in enhancing the quality of Islamic religious education. This article investigates the challenges faced by Islamic religious teachers in their professional development and explores strategies to empower them in addressing these challenges. The study combines a literature review with in-depth interviews of experienced Islamic religious teachers. Findings highlight several key challenges, including limited access to professional development resources and administrative barriers. The article also provides recommendations for improving the professional development of Islamic religious teachers through training, institutional support, and collaboration among educators. These findings have significant implications for enhancing the quality of Islamic religious education in the future.